Professional Preparation of Pre-service Teachers Post NEP-2020: Some Suggestive Changes for Quality Improvement - Dutta, Indrajeet (Voices of Teachers and Teacher Educators, 2022)
Teacher education preparation have undergone sea changes since its inception from colonial times. Most of the teacher training programs in the early phase of teacher education were influenced from western ideologies. Even after Independence, the influence of western thoughts found its place in the preparation of teacher education programs, though preparation of teachers was for Indian classrooms. Even today, foundation of teacher education program is more based on philosophical, sociological and psychological ideologies and theories which often does not suit to Indian classrooms or Indian children. More importantly, it has been highlighted in many reports that teacher preparation process is faulty and more often than not non-contextual in terms of need and aspiration of Indian children studying in various types of schools. So, it can be said that professional preparation of teachers has never risen to the level of expectations of school and society. NCF (2005) and NCFTE (2009) has questioned the practices of teacher education and raise their concerns over the ill-preparation of teachers in TEIs and recommended to overhaul the teacher preparation process. Practices of teacher education programme hasn’t changed much even after revamping of curriculum in 2014 as most of the TEIs suffer from various ill-practices which are detrimental to profession. That’s why when debate arises, whether to restructure the teacher programs, NEP-2020 comes with the solution that all teacher education institutions will no longer be stand-alone and they have to become multidisciplinary by 2030 and only four-year Integrated Teacher Education Program will be run in the country post 2030. The present paper suggests few of the imminent changes that need to be done to improve the teacher education programs in the country.